First Robotic Hepatectomy With Middle Hepatic Vein Reconstruction Using ePTFE Graft for Hepatic Adenoma: A Case Report - Wang, Jilong; Jin, Zongrui; Xu, Banghao; Chen, Weitao; Zhang, Jianyong; Zhu, Hai; Lu, Tingting; Zhang, Ling; Guo, Ya; Wen, Zhang (Frontiers in Surgery, 2022)
Surgical resection remains the best choice for treatment of liver tumors. Hepatectomy combined with artificial vascular reconstruction has been proven as an alternative to treating tumor involved with main hepatic veins. As the cutting-edge surgical technology, robotic liver surgery is a novel technique expanding the field of minimally invasive approaches, especially in complex reconstruction. This study reported, for the first time, robotic hepatectomy with middle hepatic vein (MHV) reconstruction using an ePTFE graft for patient with hepatic adenoma. The tumor, which was located in segment 8, was adjacent to MHV. Robot-assisted resection of the segment 4 and partial 8 and MHV reconstruction using ePTFE graft was performed. During the postoperative examination and follow-up, the blood flow of ePTFE graft was patent, and liver function was recovered well. Thus, robotic hepatectomy with MHV reconstruction is a safe, minimally invasive, and precise surgery that may be a novel minimally invasive approach for patients with liver tumors invading or adjacent to main hepatic veins.